The yamuna river basin : Water resources and environment - Rai, Raveendra Kumar (Water Science and Technology Library, 2012)
This book is designed to provide concepts, methodologies, and approaches for river basin studies with respect to water resources and environment. The book is not limited to the Yamuna River basin, but will help in the study of various other river basins for integrated water resources management. The book covers the essential components of integrated water resources management, including analysis of climatic variables, climate change detection, analysis of natural resources, geology, geomorphology, socio-economics, water budgeting, flood estimation, river pollution, etc. Furthermore, the book addresses recent issues pertaining to water quality, water quality indices, environmental flows, water resources mangement through cropping pattern change, etc. along  with methodologies and application to the Yamuna River system. However, the main objective of this book is to address important issues of water resources management of river basins. Audience: The manuscript has been designed so that it can be used as a reference for river basin studies. The book will be useful to engineers, agricultural scientists, environmentalists, planners, managers, and administrators who are concerned with water resources.